2010
DOI: 10.1210/edrv.31.6.9981
|View full text |Cite
|
Sign up to set email alerts
|

Antiadipogenic Effects of the Mineralocorticoid Receptor Antagonist Drospirenone: Potential Implications for the Treatment of Metabolic Syndrome

Abstract: fatty acids and minimal obesity, absent GH activation leads to steatosis because phosphorylated STAT5 prevents hepatic steatosis. These results raise the possibility of low-dose GH treatment for nonalcoholic fatty liver disease. Endocrinology, published November 17, 2010, 10.1210/en. 2010 The Somatotrope as a Metabolic Sensor: Deletion of Leptin Receptors Causes Obesity Gwen V. Childs, Noor Akhter, Anessa Haney, Mohsin Syed, Angela Odle, Michael Cozart, Zachary Brodrick, Dana Gaddy, Larry J. Suva, Nisreen Akel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…Of importance, this locally produced aldosterone might have an autocrine (patho)physiological role by influencing, among other processes, adipocyte differentiation. 16,17,19,26 Our findings demonstrate that the selective CYP11B2 inhibitor FAD286 prevented adipocyte differentiation, triacylglycerol accumulation, and expression of adipocyte differentiation markers peroxisome proliferator-activated receptor-␥ and aP2. In support of these data, MR-gene knockout adipocytes fail to accumulate lipids.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Of importance, this locally produced aldosterone might have an autocrine (patho)physiological role by influencing, among other processes, adipocyte differentiation. 16,17,19,26 Our findings demonstrate that the selective CYP11B2 inhibitor FAD286 prevented adipocyte differentiation, triacylglycerol accumulation, and expression of adipocyte differentiation markers peroxisome proliferator-activated receptor-␥ and aP2. In support of these data, MR-gene knockout adipocytes fail to accumulate lipids.…”
Section: Discussionmentioning
confidence: 54%
“…[16][17][18] Experimental and clinical studies demonstrated positive outcomes of MR blockade in obesity/diabetes mellitus-related cardiovascular and kidney disease. [19][20][21] We previously reported the presence of aldosterone in conditioned culture medium (CCM) from the 3T3-L1 adipocyte cell line.…”
mentioning
confidence: 99%
“…There is increased expression and activation of MR in adipose tissue in experimental and human obesity, diabetes, and cardiovascular diseases (6,14,15,32). 2.…”
Section: Discussionmentioning
confidence: 99%
“…Дроспиренон объединяет в себе эффекты эндогенного прогестерона (антигонадотропный и антиандрогенный) со свойствами антиминералокортикоидов, которые клинически выража-ются в уменьшении задержки жидкости и натрия в орга-низме, что способствует дополнительному снижению массы тела [10][11][12][13][14][15]. Кроме того, режим приема КОК 24/4 в сравнении с режимом 21/7 достоверно уменьшает дли-тельность и обильность планового кровотечения отмены [16], а также высокоэффективен в купировании симпто-мов при тяжелом предменструальном синдроме [13,17].…”
Section: состав и механизм действия комбинированных оральных контрацеunclassified